Effect of plant spacing and salinity of irrigation water on growth and flower yield of marigold in semi-arid conditions - Chauhan, S.K. (Annals of Agricultural Research, 2016)
A field experiment was carried out during rabi seasons of 2011-12 and 2012-13 at R.B.S.Collegeresearch farm, Bichpuri, Agra to assess the effect of planting spacing and irrigation water salinityon behavior of African marigold (Tagetes erecta Linn) cv. 'Pusa Narangi'. Maximum plant heightand secondary branches plant–1 increased at closer spacing of 50 cm × 40 cm; however, spreadand diameter of plant, primary branches plant–1 increased in wider spacing (50 cm × 50 cm).Opening of first flower was delayed in closer spacing, whereas duration of flowering and yield0.41 kg plant–1 was observed in wide spacing (50 cm × 50 cm) but yield 202.8 q ha–1 obtained incloser spacing (50 cm × 40 cm). The use of saline water in irrigation increase salinity levels reducedplant height; plant spared, and yields of flower 125.1 q ha–1 in ECiw 9 dS/m. Interaction betweenspacing and salinity levels was found non-significant in all characteristics. The net profit wasmaximum in (50 cm × 40 cm) row spacing (Rs. 50,120) and minimum in row spacing (50 cm × 50cm) (Rs. 45,920). In case of salinity the maximum net profit obtained in best available water (Rs.51,320) and lowest in Eciw 9 dS/m (Rs. 19,000) respectively.